Catalytic valorization of biomass for furfuryl alcohol by novel deep eutectic solvent-silica chemocatalyst and newly constructed reductase biocatalyst. (March 2022) - Li, Qi; Ma, Cuiluan; Di, Junhua; Ni, Jiacheng; He, Yu-Cai
Graphical abstract: Highlight: Deep eutectic solvent-silica heterogeneous catalyst was firstly used to prepare FAL. High FAL yield (45.3%) was achieved from corncob with B:LA-SG(SiO2 ) in water. Corncob-derived FAL yielded FOL at 98% yield by reductase using cosubstrate formate. Valorization of biomass to FOL was developed via chemoenzymatic cascade catalysis. Abstract: Chemoenzymatic cascade catalysis using deep eutectic solvent-silica heterogeneous catalyst and reductase biocatalyst was constructed for synthesizing furfuryl alcohol from biomass in one-pot manner. A novel heterogeneous catalyst B:LA-SG(SiO2 ) was firstly prepared by immobilizing deep eutectic solvent Betaine:Lactic acid on silica with sol–gel method using tetraethyl orthosilicate as silicon source. High furfural yield (45.3%) was achieved from corncob with B:LA-SG(SiO2 ) catalyst (2.5 wt%) in water at 170 ˚C for 0.5 h. Possible catalytic mechanism for converting biomass into furfural was proposed. Moreover, one newly constructed recombinant E. coli KF2021 cells containing formate dehydrogenase and reductase was utilized to transform corncob-valorized furfural into furfuralcohol at 97.7% yield at pH 7.5 and 40 ˚C via HCOONa-driven coenzyme regeneration. Such a hybrid process was constructed for tandem chemocatalysis and biocatalysis in a same reactor, potentially reducing the operation cost, which had potential application for valorization of biomass to value-added furans.